Internalisasi Nilai Hak Asasi Manusia dalam Kurikulum Pendidikan Islam: Studi Lapangan di MA Ainul Falah Bakeong Guluk-Guluk Sumenep - Qadariyah, Lailatul; Solichin, Mohammad Muchlis; Atiqullah; Siswanto (Lembaga Bale Literasi, 2026)
This study is motivated by the importance of integrating Human Rights values into Islamic education, which is often perceived as having a gap with the concept of human rights. Values such as justice, equality, and tolerance are inherently embedded in Islamic teachings; however, in educational practice, these values are not always systematically internalized within the curriculum. Many Islamic educational institutions still convey these values implicitly without explicitly linking them to the concept of human rights, which may lead to a partial understanding among students. This research employs a qualitative approach with a case study design conducted at MA Ainul Falah. The research subjects include the principal, teachers, and students. Data were collected through semi-structured interviews, observations of the learning process, and documentation such as lesson plans, syllabi, and school regulations. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, while data validity is ensured through source and technique triangulation. The findings indicate that the internalization of human rights values occurs through stages of understanding, internalization, and practice, which are integrated into both classroom learning and school culture. Teachers apply cognitive, affective, and psychomotor strategies in the process. The main challenges include limited teacher understanding, the absence of explicit curriculum integration, and school culture constraints, while solutions involve teacher training, curriculum integration, and strengthening an inclusive school culture.